Effect of GnRH alone or in combination with estrogen on the ovarian activity of postpartum anestrous cows - CHANDRA, POONAM; LAKHCHAURA, B D; SUD, S C; ATHEYA, U K; GARG, G K (The Indian Journal of Animal Sciences, 2013)
During the postpartum period, 2 anestrous cows were injected with 2 doses of 250 g each of gonadotropin-releasing hormone (GnRH) at 10 days interval (experiment 1) and 9 anestrous cows were injected with 5 mg estradiol valerate and 2 days later by 250 g GnRH (experiment 2). By analysing the milk progesterone patterns, it was observed that 2 doses of GnRH did not evoke any response; however, combination of estrogen and GnRU provoked high progesterone levels within 7 days in all the animals which exhibited ovarian cyclicity. Insemination of the 6 cycling cows at second or third post-treatment estrus lead to pregnancy in 5 animals.